2007
DOI: 10.1097/mph.0b013e31805d8f32
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Pulmonary Hypertension in Children With Sickle Cell Disease

Abstract: Pulmonary hypertension (PHT) affects approximately 30% of adults with sickle cell disease. Adults with PHT have a significantly higher mortality rate. We report the results of a prospective study of the prevalence of PHT among children with sickle cell disease. In our cohort, 31% of children>or=10 years of age have evidence of PHT by Doppler echocardiography. Factors associated with the presence of PHT are male sex and elevated reticulocyte count. We recommend screening all children for PHT starting at the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 28 publications
4
34
2
2
Order By: Relevance
“…Prevalence of PH was 21AE6%. This value is in the range of other prospective studies involving children during steady state, which observed a prevalence of PH ranging from 11% to 30% (Nelson et al, 2007;Pashankar et al, 2008;Minniti et al, 2009). Our data are the first to show a high prevalence of elevated TRV in very young children (see Table V).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Prevalence of PH was 21AE6%. This value is in the range of other prospective studies involving children during steady state, which observed a prevalence of PH ranging from 11% to 30% (Nelson et al, 2007;Pashankar et al, 2008;Minniti et al, 2009). Our data are the first to show a high prevalence of elevated TRV in very young children (see Table V).…”
Section: Discussionsupporting
confidence: 66%
“…On the contrary, besides the reticulocytes, other parameters of haemolysis, including degree of anaemia, lactate dehydrogenase and bilirubin levels were not different between the two groups, and other parameters of inflammation, besides the platelets, were also not different. Correlation of higher reticulocyte and platelet counts was demonstrated by other studies (Nelson et al, 2007;Pashankar et al, 2008;Lee et al, 2009), but these also failed to determine correlation with other determinants of haemolysis. In our study, the relatively small sample population could explain the lack of significance of the other markers of haemolysis or inflammation.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Some studies have found an association of high hemoglobin F with lower pulmonary hypertension risk, [11][12][13][14] but several others have detected no such association. 1,2,[15][16][17][18] We recently reported a prospective, multicenter study of 310 children and adolescents with sickle cell disease at steady state in which tricuspid regurgitation velocity of 2.6 m/s or higher occurred in 11% of participants and had independent associations with hemolysis and hemoglobin oxygen desaturation. 3 In addition, we have found that an elevated screening tricuspid regurgitation velocity in children and adolescents with sickle cell disease predicts functional impairment over 2 years of follow-up (V.R.G., unpublished observations, April 2009).…”
Section: Introductionmentioning
confidence: 99%